Process performance and life cycle assessment of friction drilling on dual-phase steel. (10th March 2019) - Pereira, O.; Urbikaín, G.; Rodríguez, A.; Calleja, A.; Ayesta, I.; López de Lacalle, L.N.
Abstract: The use of friction drilling technique for hole making in tube dual phase steels was presented in this paper as an alternative to conventional drilling techniques. Due to the higher environmental consciousness growing up in the last years in different industrial environments, the feasibility of the proposed alternative must be analyzed taking into account both, technical and environmental aspects. In order to perform a complete environmental approach for conventional drilling, different lubri-cooling technologies were tested: dry drilling, wet drilling and minimum quantity of lubrication (MQL) drilling using high-oleic sunflower oil. From the technical point of view, results show that using friction drilling, the surface quality obtained was more appropriate. The deformed material provides a perfect base for future threading or joining operations and, moreover, the thermal affected layer observed in micrographies provides a 20 μm hardened layer which reduce surface wear and damages, improving hole zone life. From the environmental point of view, a life cycle assessment (LCA) was carried out for both drilling techniques and different lubricooling environments. Results show that friction drilling presents an ecologic improvement, obtaining a notable reduction in all impact categories. Analyzing both points of view, friction drilling is presented as a solution that improves current drilling processes of metal sheets. Highlights: Friction drilling is presented as a new technology to drilling tubes without cutting fluids. A technical comparison with conventional drilling shows the suitability of friction drilling. The LCA performed shows the eco-efficiency benefits of the proposed solution.